The cultural dimension of the symbol in contemporary Iraqi painting (Journal of the College of Basic Education, 2022)
The research aims to identify the cultural dimension of the symbol in contemporary Iraqi painting, to know the divisions of the symbol in the light of its culture, starting from the employment of environmental localism to psychological, cultural and mythological symbols as symbols that contributed to the manufacture of cultural features produced by Iraqi painting. This research included three investigations, the first of which included multi-dimensionality Symbolism, while the second topic referred to the characteristics of the cultural symbol, while the third topic dealt with the cultural symbol in contemporary Iraqi painting.